Plasma-Coated Polycaprolactone Nanofibers with Covalently Bonded Platelet-Rich Plasma Enhance Adhesion and Growth of Human Fibroblasts - Miroshnichenko, Svetlana; Timofeeva, Valeriia; Permykova, Elizaveta; Ershov, Sergey; Kiryukhantsev-Korneev, Philip; Dvořaková, Eva; Shtansky, Dmitry V; Zajíčková, Lenka; Solovieva, Anastasiya; Manakhov, Anton (Nanomaterials (Basel, Switzerland), 2019)
Biodegradable nanofibers are extensively employed in different areas of biology and medicine, particularly in tissue engineering. The electrospun polycaprolactone (PCL) nanofibers are attracting growing interest due to their good mechanical properties and a low-cost structure similar to the extracellular matrix. However, the unmodified PCL nanofibers exhibit an inert surface, hindering cell adhesion and negatively affecting their further fate. The employment of PCL nanofibrous scaffolds for wound healing requires a certain modification of the PCL surface. In this work, the morphology of PCL nanofibers is optimized by the careful tuning of electrospinning parameters. It is shown that the modification of the PCL nanofibers with the COOH plasma polymers and the subsequent binding of NH2 groups of protein molecules is a rather simple and technologically accessible procedure allowing the adhesion, early spreading, and growth of human fibroblasts to be boosted. The behavior of fibroblasts on the modified PCL surface was found to be very different when compared to the previously studied cultivation of mesenchymal stem cells on the PCL nanofibrous meshes. It is demonstrated by X-ray photoelectron spectroscopy (XPS) that the freeze-thawed platelet-rich plasma (PRP) immobilization can be performed via covalent and non-covalent bonding and that it does not affect biological activity. The covalently bound components of PRP considerably reduce the fibroblast apoptosis and increase the cell proliferation in comparison to the unmodified PCL nanofibers or the PCL nanofibers with non-covalent bonding of PRP. The reported research findings reveal the potential of PCL matrices for application in tissue engineering, while the plasma modification with COOH groups and their subsequent covalent binding with proteins expand this potential even further. The use of such matrices with covalently immobilized PRP for wound healing leads to prolonged biological activity of the immobilized molecules and protects these biomolecules from the aggressive media of the wound.
Keywords: cell viability; freeze–thawed platelet-rich plasma immobilization; polycaprolactone; nanofibers; cell adhesion and spreading; COOH plasma